Functionalized 3D scaffolds for engineering the hematopoietic niche - Bruschi, Michela; Vanzolini, Tania; Sahu, Neety; Balduini, Alessandra; Magnani, Mauro; Fraternale, Alessandra (Frontiers in Bioengineering and Biotechnology, 2022)
Hematopoietic stem cells (HSCs) reside in a subzone of the bone marrow (BM) defined as the hematopoietic niche and where, via interplay of differentiation and self-renewal, they are able to give rise to immune and blood cells. Artificial hematopoietic niches were firstly developed in 2D in vitro cultures but the limited expansion potential and stemness maintenance induced the optimization of these systems to avoid the total loss of the natural tissue complexity. Next steps were adopted by engineering different materials such as hydrogels, fibrous structures with natural or synthetic polymers, ceramics, etc. to produce a 3D substrate better resembling that of BM. Cytokines, soluble factors, adhesion molecules, extracellular matrix (ECM) components but also the secretome of other niche-resident cells play a fundamental role in controlling and regulating HSCs commitment. To provide certain cues, it became necessary the use of co-cultures or feeder-layer and the application of natural or synthetic molecules as medium supplement or as coating. This review gathers key elements employed for the functionalization of a 3D scaffold that demonstrated to promote HSCs growth and differentiation ranging from (i) biophysical cues, i.e., material, topography, stiffness, oxygen tension and fluid shear stress to (ii) biochemical hints favored by the presence of ECM elements, feeder cell layers and redox scavengers. Particular focus is given to 3D system to recreate megakaryocyte products, to be applied for blood cell production, whereas HSCs clinical application in such 3D constructs were limited so far to BM diseases testing.